Formation Mechanism of MgO Containing Inclusions in the Molten Steel Refined in MgO Refractory Crucibles - Yiyan Li; Wen Yang; Lifeng Zhang (Metals, 2020)
In order to study the influence of MgO refractory on inclusions during the steelmaking process, laboratory quasi-equilibrium experiments were performed in MgO crucibles at 1873 K. It was found that there were no MgO-containing inclusions formed when ultra-low Al ultra-low C steel was used. When the contents of dissolved Al and C in steel changed, different composition ranges led to different types of inclusions. It was shown as well that for both low Al high C steel and high Al low C steel, the order of average MgO content in inclusions from large to small was: MgO-10% slag addition > MgO-free slag addition > no slag addition. Based on the results, a simple formation mechanism of MgO-containing inclusions in the steel with different compositions in MgO crucibles was proposed. The results could provide guidance for the reduction of MgO-containing inclusions in the industrial production of steels.